The similarities and differences between the empirical and experimental data: investigation on the single-lane traffic. Issue 1 (23rd December 2019) - Jin, Cheng-Jie; Jiang, Rui; Liang, Hong-Feng; Li, Dawei; Wang, Hao
ABSTRACT: In order to check whether the results of traffic experiments can reveal the empirical traffic conditions, this study discusses the similarities and differences between them. The empirical data come from the special single-lane traffic when one lane is temporarily closed during the maintenance work. The experimental data are obtained from the platoons in one experiment under open boundary condition. Three perspectives are used for checking: the statistics of all the platoons, the evolution of stable platoons and the characteristics of four important traffic flow distributions (velocity, time-headway, velocity difference and time-headway difference at continuous locations). We find in all these areas, the empirical data and the experimental data are qualitatively similar. But the quantitative differences could be measured, e.g. the oscillation amplitude of traffic parameters in the experiment is usually larger. These results can help to improve the quality of traffic experiments in the future.